(untitled) (diségno, 2022)
The Politecnico di Torino has undertaken actions to promote and disseminate its historical archival heritage as a unitary system of technical knowledge and information. The critical use of dedicated management methodologies and information technologies is the cornerstone for the enhancement of its repositories. The contribution illustrates the preparation of a web-based distributed information system that links together the apparatus of the Archivio G.A. Porcheddu in the period 1894 to 1994. Porcheddu in the period 1894 to1927 –Agent and General Concessionaire for Upper Italy of the system patented by François Hennebique– kept at the Department of Structural, Geotechnical and Builiding Engineering of the Politecnico di Torino. These heritages are rich in conceptual elements, brought to life by specially designed graphic supports, which effectively exploit the performance of digital technologies and restore value to the most recent studies on the City through more efficient processes of sharing.